Gestão acadêmica em tempos de regulação transnacional e financeirização da educação superior: um estudo sobre duas corporações de ensino superior - Carvalho Júnior, Raimundo Nonato de (2022)
The present work analyzes the impacts of transnational regulation and financialization on the academic management of Brazilian higher education institutions, using to study the cases of two large national corporations that operate in the sector: Estácio and Kroton Educacional, groups that, from the years 2000, a strategy to expand its presence in the Brazilian national higher education system through market operations, including the sale of assets and the opening of shares in the financial market. For that, a research was developed in three dimensions: documentary, bibliographical and empirical. The documentary research was dedicated to understanding the guidelines that supported the proposition of mercantile privatization policies in the sector in Brazil, as proposed in educational documents from multilateral agencies such as the World Bank and OECD, and the legal regulation that promoted liberalizing changes in the policy of higher education opening it up to entrepreneurship and investment in the financial markets. The bibliographic research focused the scientific production around the three fundamental categories that integrate the market strategy of such groups: transnational regulation, mercantile privatization and academic management, constituting a literature review of the main theoretical references that attempt to analyze the contemporary trends of reconfiguration of higher education in the country. The empirical research was based on interviews, based on a semi-structured script, with managers of the institutions involved in this investigation, in order to understand the impacts on the academic management of the HEIs in which they operate, emphasizing the analysis of the perceptions of these actors in relation to changes in the provision of services. educational services and the new post-merger and acquisition organizational culture. The study demonstrates that academic management, a central part of the organization that constitutes and expresses the institutional identity, is impacted by the reflexes of transnational regulation, mercantile privatization and institutional policies of large educational corporations that operate the higher education market, in such a way that that, progressively, new visions about mission, vision and values in the sector are established.